2015
DOI: 10.1163/15685411-00002916
|View full text |Cite
|
Sign up to set email alerts
|

Mononchoides macrospiculum n. sp. (Nematoda: Neodiplogastridae) and Teratorhabditis synpapillata Sudhaus, 1985 (Nematoda: Rhabditidae): nematode associates of Rhynchophorus ferrugineus (Oliver) (Coleoptera: Curculionidae) in Italy

Abstract: Several juvenile and adult nematodes were isolated after dissection of pupae and adults of the red palm weevil,Rhynchophorus ferrugineus, recovered from an infestedPhoenix canariensisChabaud exemplar in Bari, Italy. Two species of nematodes were recovered,Teratorhabditis synpapillataandMononchoides macrospiculumn. sp. which is described herein. The mitochondrial cytochrome oxidase I (COI), the ITS-containing region, the 18S rRNA gene (SSU) and the D2-D3 expansion domains of the 28S rRNA gene (LSU) were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…The present study confirmed the co‐occurrence of two phoretic nematode species, T. synpapillata and M. macrospiculum , associated with RPW at all sampling sites (Troccoli et al, ) and provided information regarding other nematodes potentially associated with RPW in southern Italy. Individual insects can simultaneously harbor more than one nematode genus (Grucmanová, Holuša, Čermák, & Nermut, ; Kanzaki et al, ; Shimizu et al, ); R. palmarum and R. cruentatus are reported to host several nematode associates, including Teratorhabditis and Mononchoides spp.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The present study confirmed the co‐occurrence of two phoretic nematode species, T. synpapillata and M. macrospiculum , associated with RPW at all sampling sites (Troccoli et al, ) and provided information regarding other nematodes potentially associated with RPW in southern Italy. Individual insects can simultaneously harbor more than one nematode genus (Grucmanová, Holuša, Čermák, & Nermut, ; Kanzaki et al, ; Shimizu et al, ); R. palmarum and R. cruentatus are reported to host several nematode associates, including Teratorhabditis and Mononchoides spp.…”
Section: Discussionsupporting
confidence: 85%
“…(Esparza‐Diaz et al, ; Kanzaki et al, , , ; Mazza et al, ; Sudhaus et al, ). This finding confirmed the possibility of vertical transmission between Teratorhabditis and Mononchoides nematode genera and the insect genus Rhynchophorus (Kanzaki et al, ; Troccoli et al, ), suggesting that the ecological niche plays an important role in shaping the nematode community of Rhynchophorus spp. Furthermore, this result suggests an important role for both nematode genera in supporting RPW during palm tree attacks.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These are Mononchoides sp. NK-2017 isolated from the palmetto weevil Rhynchophorus cruentatus 12 , M. macrospiculatum isolated from the red palm weevil R. ferrugineus 13 , M. compositicola 14 and M. striatus . The LT diplogastrid morphospecies is clearly a putative new species closest to or sister with C. manati that shares highly derived stomatal morphology and an association with the Florida manatee but should probably be reconsidered as a highly derived Mononchoides, not part of a separate genus ( Cutidiplogaster ) (Fig.…”
Section: Resultsmentioning
confidence: 99%